Topographic peculiarities of central serous chorioretinopathy depending on the form of the diseases and infection with the causative agent helicobacter pylory (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The frequency of Helicobacter Pylori (HP) infection among patients with central serous chorioretinopathy (CSC) exceeds general national one.Purpose. To determine tomographic peculiarities of the central serous chorioretinopathy depending on the form of the disease and Helicobacter Pylori infection.Materials and methods. 93 patients with acute form, 15 — with primary chronic and 36 (44 eyes) with secondary chronic form of central serous chorioretinopathy were examined with the help of spectral OCT on the tomograph «SOCT Copernicus».Results. HP-positive patients with CSC are characterized by: frequency of combined neuro- and pigment retinal epithelium detachment (15.9 % eyes) was 2.1 times higher (p
Keywords: central serous chorioretinopathy; acute form; chronic form; retinal tomography; Helicobacter Pylori